The association of cell adhesion molecules and selectins (VCAM-1, ICAM-1, E-selectin, L-selectin, and P-selectin) with microvascular complications in patients with type 2 diabetes: A follow-up study - Siddiqui, Khalid; George, Teena P.; Mujammami, Muhammad; Isnani, Arthur; Alfadda, Assim A. (Frontiers in Endocrinology, 2023)
Objective: Chronic hyperglycemia induces pathogenic changes in the vascular endothelium and leads to the development of microvascular complications in patients with type 2 diabetes mellitus. Early identification of markers of diabetes complications may help to minimize the risk of the development and progression of microvascular complications. Methods: This follow-up study was conducted in type 2 diabetic cohort aged between 30-70 years. Out of 160 eligible participants, 70 of them completed follow-up. Levels of cell adhesion molecules and selectins (VCAM-1, ICAM-1, E-selectin, L-selectin and P-selectin) at baseline and follow-up were measured using Randox Evidence biochip analyzer (UK). Development of microvascular complications (diabetic neuropathy, retinopathy and nephropathy) was evaluated. Results: During the follow-up (2 years, median), 31 (44.3%) developed diabetic neuropathy, 10 (14.3%) developed diabetic retinopathy and, 27 (38.6%) developed diabetic nephropathy. A significant difference in levels of cell adhesion molecules and selectins were found in type 2 DM patients with and without microvascular complication. Multiple logistic regression analysis revealed that the baseline level of VCAM-1 was significantly associated with microvascular complications; diabetic neuropathy(p=0.028), retinopathy (p=0.007) and nephropathy(p=<0.001). Additionally, levels of P-selectin (p=0.05) and L-selectin (p=0.008) was associated with diabetic nephropathy while retinopathy was associated with L-selectin(p=0.005). Conclusion: Cell adhesion molecules and selectins are indicators of microvascular complication. Association of these markers with the development of microvascular complications may provide additive information for developing strategies for diabetes management and prediction of microvascular complications